A CuCoO2 / Cu2O quantum dot composite material and its preparation method
Patent Information
- Application Number
- CN202610925475.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
AI Technical Summary
但是,由于CuCoO2材料的特殊性质,传统常用方法均无法制备性能较为优异的CuCoO2/Cu2O量子点复合材料:
1.本发明制备方法能够有效规避CuCoO2基底在制备量子点复合材料过程中容易产生热分解、形成表面电荷干扰、形成杂相等问题,从而首次成功制备纯净度较高、结构完整、界面良好的CuCoO2/Cu2O量子点复合材料。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of quantum dot composite material technology, and relates to a CuCoO2 / Cu2O quantum dot composite material and its preparation method. Background Technology
[0002] Quantum dots are a special type of zero-dimensional nanomaterial. They are generally spherical, with a diameter no larger than the exciton Bohr diameter of the corresponding semiconductor material, and their size is generally between 1 and 10 nm.
[0003] Quantum dots, as an important semiconductor nanomaterial, have shown great application potential in fields such as photoelectric conversion, bioimaging, catalysis, and sensing due to their unique optical and electrical properties (such as size-tunable fluorescence emission, high quantum yield, and excellent charge transport performance).
[0004] However, pure quantum dots suffer from poor stability and easy aggregation, which severely restricts their practical applications. To overcome these problems, quantum dots are usually loaded onto specific substrate materials (such as oxides, polymers, and carbon materials) to construct quantum dot-based nanocomposites. This enhances their stability and dispersibility, and fully utilizes the excellent properties of each component, thereby significantly improving the overall performance of the material. Among these, heterojunction nanocomposites composed of CuCoO2 as the substrate material and Cu2O quantum dots have broad application prospects in photocatalysis and electrochemistry due to their band structure matching and high interfacial charge transfer efficiency.
[0005] Currently, common methods for preparing quantum dot-based nanocomposites include solvothermal methods, self-assembly methods, and chemical vapor deposition methods. However, due to the special properties of CuCoO2, traditional methods cannot prepare CuCoO2 / Cu2O quantum dot composites with superior performance. Chemical vapor deposition typically requires high deposition temperatures, but CuCoO2 is prone to phase transition or thermal decomposition within the chemical vapor deposition temperature range, leading to irreversible damage to the substrate structure and making it impossible to obtain a complete heterojunction interface.
[0006] CuCoO2 has a layered crystal structure, which makes it prone to interlayer delamination or lattice distortion in polar solvents under solvothermal conditions. Furthermore, it is difficult to precisely control the nucleation and growth kinetics of Cu2O quantum dots during the reaction process, which easily generates impurities such as CuO or metallic Cu, making it impossible to obtain pure phase composite materials.
[0007] When preparing composite materials using electrostatic self-assembly, the substrate material and the quantum dot surface must have opposite charges. However, the surface charge density and polarity of CuCoO2 in aqueous solution or organic solvent are extremely sensitive to pH value and solvent type, making it difficult to stably meet the conditions for electrostatic attraction with Cu2O quantum dots, thus making assembly difficult.
[0008] When Cu2O quantum dots are directly grown on a CuCoO2 substrate via a chemical reaction, since CuCoO2 also contains Cu... + and Co 3+ During the reaction, ion exchange or competitive reduction reactions are prone to occur, inevitably introducing cobalt oxide or copper-cobalt composite impurities. This results in poor controllability of the reaction process and ultimately causes a large number of impurities in the composite material, affecting its performance.
[0009] Therefore, it is necessary to provide a CuCoO2 / Cu2O quantum dot composite material and its preparation method to efficiently and controllably prepare CuCoO2 / Cu2O quantum dot nanocomposites with superior performance and high stability. Summary of the Invention
[0010] To overcome the problems in the prior art, the present invention drives the uniform mixing of Cu2O quantum dots and CuCoO2 substrate through grinding. During the grinding process, the solvent continuously evaporates, which ultimately promotes the formation of physical contact between the quantum dots and the substrate. Then, low-temperature annealing promotes the formation of a stable physicochemical composite at the interface between the quantum dots and the substrate, thereby obtaining a pure, stable CuCoO2 / Cu2O quantum dot composite material with excellent interface.
[0011] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention provides a method for preparing CuCoO2 / Cu2O quantum dot composite materials, the method comprising the following steps: (1) Disperse Cu2O quantum dots in a solvent and perform ultrasonic treatment to obtain a Cu2O quantum dot dispersion solution, wherein oil-soluble Cu2O quantum dots are dispersed in an oily solvent and water-soluble Cu2O quantum dots are dispersed in water or alcohol.
[0012] Since the solvent does not participate in the reaction, its amount is sufficient to fully disperse the Cu2O quantum dots, and excess solvent can be used.
[0013] (2) Add Cu2O to the Cu2O in step (1) CuCoO2 powder was added to the quantum dot dispersion solution, and then the solution was ground until all the solvent evaporated to obtain a dry powder.
[0014] (3) In an inert gas atmosphere, the dried powder in step (2) is subjected to low-temperature annealing to obtain CuCoO2 / Cu2O quantum dot composite material.
[0015] Preferably, in step (1), the oily solvent includes one of petroleum ether, n-hexane, cyclohexane, toluene, and chloroform.
[0016] Preferably, in step (1), the alcohol includes one of ethanol, methanol, and isopropanol.
[0017] Preferably, in step (2), the mass ratio of CuCoO2 powder to Cu2O quantum dots is CuCoO2:Cu2O = 4:1~19:1.
[0018] Preferably, in step (3), the annealing temperature is 300-400℃ and the holding time is 1.5-2.5h.
[0019] Preferably, in step (1), the specific preparation process of oil-soluble Cu2O quantum dots includes the following steps: S1: Dissolve Cu(NO3)2·3H2O in ethylene glycol, add polyvinylpyrrolidone and oleic acid, sonicate and stir to make the solution homogeneous.
[0020] A solution is considered homogeneous if Cu(NO3)2·3H2O, polyvinylpyrrolidone, and oleic acid are completely dissolved in ethylene glycol.
[0021] The solid-liquid ratio of Cu(NO3)2·3H2O to ethylene glycol is Cu(NO3)2·3H2O: ethylene glycol = 1 mmol: 20~30 mL. Polyvinylpyrrolidone is added for every 1 mmol of Cu(NO3)2·3H2O and 0.5 mL of oleic acid is added for every 1 mmol of Cu(NO3)2·3H2O.
[0022] S2: Add sodium borohydride solution dropwise to the solution in step S1, stir until the reaction is complete, wash and dry the reaction product to obtain oil-soluble Cu2O quantum dots.
[0023] The stirring speed is 700~900 r / min, and the reaction time is 20~30 min.
[0024] The concentration of the sodium borohydride solution is ≥0.02 g / mL. The sodium borohydride solution is added to the solution in step S1 at a rate of 0.15 g of sodium borohydride per 1 mmol Cu(NO3)2·3H2O.
[0025] Sodium borohydride solution is a solution prepared by adding sodium borohydride to water. The amount of water used should be just enough to completely dissolve the sodium borohydride, but the amount of water should not be too much to avoid the solution concentration being too low and affecting the reducing properties of sodium borohydride solution.
[0026] Preferably, step (1), the specific preparation process of water-soluble Cu2O quantum dots includes the following steps: Q1: Dissolve Cu(NO3)2·3H2O in ethylene glycol, add polyvinylpyrrolidone and oleic acid, sonicate and stir to make the solution homogeneous.
[0027] The solid-liquid ratio of Cu(NO3)2·3H2O to ethylene glycol is Cu(NO3)2·3H2O: ethylene glycol = 1 mmol: 20~30 mL. Polyvinylpyrrolidone is added for every 1 mmol of Cu(NO3)2·3H2O and 0.5 mL of oleic acid is added for every 1 mmol of Cu(NO3)2·3H2O.
[0028] Q2: Add sodium borohydride solution dropwise to the solution in step Q2, stir until the reaction is complete, wash and dry the reaction product I, and then disperse the reaction product I in n-hexane to obtain a solution of reaction product I.
[0029] Hexane does not participate in the reaction; the amount used should be sufficient to fully disperse reaction product I, and an excess is acceptable.
[0030] The stirring speed is 700~900 r / min, and the reaction time is 20~30 min.
[0031] The concentration of the sodium borohydride solution is ≥0.02 g / mL. The sodium borohydride solution is added to the solution in step Q1 at a rate of 0.15 g of sodium borohydride per 1 mmol Cu(NO3)2·3H2O.
[0032] Q3: Dissolve 3-mercaptopropionic acid in methanol to obtain a 3-mercaptopropionic acid solution. Add the reaction product I solution from step Q2 dropwise to the 3-mercaptopropionic acid solution, and add acetone at the same time. After the reaction is completed, wash and dry the reaction product II to obtain water-soluble Cu2O quantum dots.
[0033] The solid-liquid ratio of 3-mercaptopropionic acid to methanol is 3-mercaptopropionic acid:methanol = 0.1 mmol:5 mL, the molar ratio of the amount of reaction product I added to 3-mercaptopropionic acid is reaction product I:3-mercaptopropionic acid = 1:0.2, and the volume of acetone added is 3-4 times the volume of methanol.
[0034] Preferably, in step (2), the specific preparation process of CuCoO2 powder includes the following steps: A: Dissolve Cu(NO3)2·3H2O and Co(NO3)2·6H2O in a mixture of water and ethanol, and stir to obtain a homogeneous solution.
[0035] After stirring, if all the solid Cu(NO3)2·3H2O and Co(NO3)2·6H2O dissolve in the mixture, the solution can be considered homogeneous.
[0036] The molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O is 1:1. In the mixture, the volume ratio of water to ethanol is water:ethanol = 2:3. The total amount of Cu(NO3)2·3H2O and Co(NO3)2·6H2O added to the mixture of water and ethanol has a solid-liquid ratio of 3 mmol:7 mL.
[0037] B: Add sodium hydroxide to the homogeneous solution in step A and stir to obtain the reaction precursor.
[0038] Stir until all sodium hydroxide is dissolved in a homogeneous solution, then stop stirring to obtain the reaction precursor.
[0039] The molar ratio of sodium hydroxide added to Cu(NO3)2·3H2O is NaOH:Cu(NO3)2·3H2O = 22:3.
[0040] C: The reaction precursor in step B is subjected to a hydrothermal reaction to obtain a precipitate. The precipitate is washed and dried to obtain CuCoO2 powder.
[0041] The hydrothermal reaction temperature is 120~160℃, and the reaction time is 24~36h.
[0042] In another aspect, the present invention provides a CuCoO2 / Cu2O quantum dot composite material prepared by the above preparation method, wherein Cu2O quantum dots are loaded onto CuCoO2 in the CuCoO2 / Cu2O quantum dot composite material.
[0043] The beneficial effects of this invention are: 1. The preparation method of the present invention can effectively avoid the problems of thermal decomposition, surface charge interference, and impurity phase formation that are easily generated in the preparation of quantum dot composite materials on CuCoO2 substrate. Thus, for the first time, CuCoO2 / Cu2O quantum dot composite materials with high purity, complete structure, and good interface are successfully prepared.
[0044] 2. In the preparation process, this invention can ensure the integrity of the CuCoO2 substrate material and the Cu2O quantum dot structure, and maintain their original physicochemical properties.
[0045] 3. The preparation method of the present invention can promote the atomic diffusion and migration of Cu2O quantum dots in a relatively mild way, thereby enabling the quantum dots to form a stable physicochemical bond with the substrate interface, strengthening the interfacial bonding force, and avoiding the generation of impurity phases by ion exchange reaction.
[0046] 4. Both oil-soluble and water-soluble quantum dot materials can be prepared into high-quality quantum dot composite materials using the preparation method of this invention. The preparation method of this invention has a wide range of applications and strong applicability.
[0047] 5. The preparation process of this invention is simple, does not require high temperature and high pressure, does not require expensive equipment, has low cost, can use low toxicity reagents, meets the requirements of green chemistry, and is suitable for industrial promotion and application. Attached Figure Description
[0048] Figure 1 The images show the XRD patterns of the oil-soluble Cu2O quantum dots, CuCoO2 substrate, and CuCoO2 / Cu2O quantum dot composite material prepared in Example 1 of this invention. Figure 2 The XRD patterns of the water-soluble Cu2O quantum dots, CuCoO2 substrate, and CuCoO2 / Cu2O quantum dot composite material prepared in Example 2 of this invention are shown. Figure 3 The figures show the performance curves of photocatalytic degradation of tetracycline hydrochloride on CuCoO2 substrate and CuCoO2 / Cu2O quantum dot composite material in Example 1 of this invention.
[0049] Figure 4 The figures show the performance curves of the CuCoO2 substrate and CuCoO2 / Cu2O quantum dot composite material prepared in Example 2 and the comparative example of the present invention for photocatalytic degradation of tetracycline hydrochloride.
[0050] Figure 5 The image shows the performance curves of photocatalytic degradation of tetracycline hydrochloride on CuCoO2 substrate and CuCoO2 / Cu2O quantum dot composite material in Example 4 of this invention. Detailed Implementation
[0051] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited to the content described.
[0052] Unless otherwise specified in the embodiments and comparative examples of this invention, the chemical reagents used in the experiments were commercially available analytical grade reagents.
[0053] Example 1 This embodiment prepares CuCoO2 / Cu2O quantum dot composite materials using the following method: (1) Preparation of Cu2O quantum dots: ① Weigh 1 mmol Cu(NO3)2·3H2O and dissolve it in 20 mL of ethylene glycol. Add 0.5 g PVP and 0.5 mL of oleic acid, and sonicate and stir to make the solution homogeneous.
[0054] ② Weigh 0.15g of sodium borohydride and dissolve it in 5mL of deionized water to obtain a sodium borohydride solution. Add the sodium borohydride solution dropwise to the solution in ① and stir at 800r / min for 25min until the reaction is complete. After the reaction is complete, disperse the reaction product in n-hexane, then add anhydrous ethanol for flocculation, followed by centrifugation and washing. Repeat the centrifugation and washing process 6 times, and then dry the reaction product to obtain oil-soluble Cu2O quantum dots.
[0055] (2) Preparation of CuCoO2 powder: ① Dissolve 15 mmol Cu(NO3)2·3H2O and 15 mmol Co(NO3)2·6H2O in a mixture of 28 mL deionized water and 42 mL ethanol, and stir to form a homogeneous solution.
[0056] ② Add 4.4 g (110 mmol) of sodium hydroxide to the homogeneous solution and stir until the sodium hydroxide is completely dissolved to form the reaction precursor.
[0057] ③ The reaction precursor was placed in a polytetrafluoroethylene high-temperature reactor and sealed. The reactor was then placed in an oven set at 140℃ and kept at that temperature for 24 hours. After the reaction was complete, the reaction product was allowed to cool, and the supernatant was poured off. The precipitate was washed six times alternately with deionized water and anhydrous ethanol. After washing, the precipitate was placed in an oven at 50℃ and dried for 12 hours to obtain pure CuCoO2 powder.
[0058] (3) Preparation of CuCoO2 / Cu2O quantum dot composite materials: ① Weigh 0.023g of Cu2O quantum dots and place them in a centrifuge tube. Add 3mL of n-hexane and use sonication until no aggregated Cu2O quantum dots are observed in the solution, thus obtaining a uniformly dispersed Cu2O quantum dot dispersion solution.
[0059] ② Pour the Cu2O quantum dot dispersion solution into a mortar, add 0.25g of CuCoO2 powder, and grind the solution to ensure uniform mixing of the Cu2O quantum dots and the CuCoO2 powder substrate. During the grinding process, the solvent gradually evaporates to allow the solid particles to come into physical contact.
[0060] ③ After grinding until the solvent has completely evaporated, a dry powder is obtained. The dry powder is transferred to a crucible and placed in a tube furnace. Under a nitrogen atmosphere, it is heated to 400℃ at a heating rate of 5℃ / min and held at this temperature for 2 hours to promote good bonding between the quantum dots and the substrate material. After the sample cools naturally, the CuCoO2 / Cu2O quantum dot nanocomposite material is obtained.
[0061] The photocatalytic degradation performance of this composite material for tetracycline hydrochloride is as follows: Figure 3As shown, the photocatalytic degradation performance of the prepared CuCoO2 / Cu2O quantum dot nanocomposite material is superior to that of pure phase CuCoO2.
[0062] Example 2 This embodiment uses the same method as Example 1 to prepare CuCoO2 / Cu2O quantum dot nanocomposite material, the difference being that: this embodiment uses water-soluble Cu2O quantum dots, and Cu2O is added to water to obtain a uniformly dispersed Cu2O quantum dot dispersion solution.
[0063] This embodiment prepares water-soluble Cu2O quantum dots using the following method: (1) Weigh 1 mmol Cu(NO3)2·3H2O and dissolve it in 20 mL of ethylene glycol. Add 0.5 g PVP and 0.5 mL of oleic acid, and sonicate and stir to make the solution uniform.
[0064] (2) Weigh 0.15g of sodium borohydride and dissolve it in 5mL of deionized water to obtain a sodium borohydride solution. Add the sodium borohydride solution dropwise to the solution in ① and stir at 800r / min for 25min until the reaction is complete. After the reaction is complete, disperse the reaction product in n-hexane, then add anhydrous ethanol for flocculation, and then centrifuge and wash. Repeat the centrifugation and washing 6 times. Then dry the reaction product to obtain reaction product I. Disperse reaction product I in n-hexane to obtain reaction product I solution.
[0065] (3) Dissolve 0.1 mmol of 3-mercaptopropionic acid in 5 mL of methanol to obtain a 3-mercaptopropionic acid solution. Add the solution of reaction product I containing 0.5 mmol of reaction product I to the 3-mercaptopropionic acid solution. At the same time, add 15 mL of acetone for flocculation. After flocculation, wash reaction product II three times with acetone and deionized water respectively. Dry reaction product II to obtain water-soluble Cu2O quantum dots.
[0066] The photocatalytic degradation performance of this composite material for tetracycline hydrochloride is as follows: Figure 4 As shown, the photocatalytic degradation performance of the prepared CuCoO2 / Cu2O quantum dot nanocomposite material is superior to that of pure phase CuCoO2.
[0067] Example 3 This embodiment prepares CuCoO2 / Cu2O quantum dot composite materials using the following method: (1) Preparation of Cu2O quantum dots: ① Weigh 1 mmol Cu(NO3)2·3H2O and dissolve it in 30 mL of ethylene glycol. Add 0.5 g PVP and 0.5 mL of oleic acid, and sonicate and stir to make the solution homogeneous.
[0068] ② Weigh 0.15g of sodium borohydride and dissolve it in 3.75mL of deionized water to obtain a sodium borohydride solution. Add the sodium borohydride solution dropwise to the solution in ① and stir at 700r / min for 30min until the reaction is complete. After the reaction is complete, disperse the reaction product in n-hexane, then add anhydrous ethanol for flocculation, followed by centrifugation and washing. Repeat the centrifugation and washing process 6 times. Then dry the reaction product to obtain reaction product I. Disperse reaction product I in n-hexane to obtain reaction product I solution.
[0069] ③ Dissolve 0.1 mmol of 3-mercaptopropionic acid in 5 mL of methanol to obtain a 3-mercaptopropionic acid solution. Add the solution of reaction product I containing 0.5 mmol of reaction product I to the 3-mercaptopropionic acid solution, and add 20 mL of acetone for flocculation. After flocculation, wash reaction product II three times with acetone and deionized water respectively. Dry reaction product II to obtain water-soluble Cu2O quantum dots.
[0070] (2) Preparation of CuCoO2 powder: ① Dissolve 15 mmol Cu(NO3)2·3H2O and 15 mmol Co(NO3)2·6H2O in a mixture of 28 mL deionized water and 42 mL ethanol, and stir to form a homogeneous solution.
[0071] ② Add 4.4 g (110 mmol) of sodium hydroxide to the homogeneous solution and stir until the sodium hydroxide is completely dissolved to form the reaction precursor.
[0072] ③ The reaction precursor was placed in a polytetrafluoroethylene high-temperature reactor and sealed. The reactor was then placed in an oven set at 120°C and kept at that temperature for 36 hours. After the reaction was complete, the reaction product was cooled, and the supernatant was poured off. The precipitate was washed six times alternately with deionized water and anhydrous ethanol. After washing, the precipitate was placed in an oven at 50°C and dried for 12 hours to obtain pure CuCoO2 powder.
[0073] (3) Preparation of CuCoO2 / Cu2O quantum dot composite materials: ① Weigh 0.055g of Cu2O quantum dots and place them in a centrifuge tube. Add 3mL of ethanol and use sonication to treat the solution until no aggregated Cu2O quantum dots are observed in the solution, thus obtaining a uniformly dispersed Cu2O quantum dot dispersion solution.
[0074] ② Pour the Cu2O quantum dot dispersion solution into a mortar, add 0.22g of CuCoO2 powder, and grind the solution to ensure uniform mixing of the Cu2O quantum dots and the CuCoO2 base material. During the grinding process, the solvent gradually evaporates to allow the solid particles to come into physical contact.
[0075] ③ After grinding until the solvent has completely evaporated, a dry powder is obtained. The dry powder is transferred to a crucible and placed in a tube furnace. Under a nitrogen atmosphere, it is heated to 300℃ at a heating rate of 5℃ / min and held at this temperature for 2.5h to promote good bonding between the quantum dots and the substrate material. After the sample cools naturally, the CuCoO2 / Cu2O quantum dot nanocomposite material is obtained.
[0076] The CuCoO2 / Cu2O composite material prepared by this method has a stronger photocatalytic degradation rate than the pure phase CuCoO2, but its photocatalytic performance is slightly lower than that of the composite material prepared in Example 2.
[0077] Example 4 This embodiment prepares CuCoO2 / Cu2O quantum dot composite materials using the following method: (1) Preparation of Cu2O quantum dots: ① Weigh 1 mmol Cu(NO3)2·3H2O and dissolve it in 25 mL of ethylene glycol. Add 0.5 g PVP and 0.5 mL of oleic acid, and sonicate and stir to make the solution homogeneous.
[0078] ② Weigh 0.15g of sodium borohydride and dissolve it in 7.5mL of deionized water to obtain a sodium borohydride solution. Add the sodium borohydride solution dropwise to the solution in ① and stir at 900r / min for 20min until the reaction is complete. After the reaction is complete, disperse the reaction product in n-hexane, then add anhydrous ethanol for flocculation, followed by centrifugation and washing. Repeat the centrifugation and washing process 6 times. Then dry the reaction product to obtain reaction product I. Disperse reaction product I in n-hexane to obtain reaction product I solution.
[0079] ③ Dissolve 0.1 mmol of 3-mercaptopropionic acid in 5 mL of methanol to obtain a 3-mercaptopropionic acid solution. Add the solution of reaction product I containing 0.5 mmol of reaction product I to the 3-mercaptopropionic acid solution, and add 17.5 mL of acetone for flocculation. After flocculation, wash reaction product II three times with acetone and deionized water respectively. Dry reaction product II to obtain water-soluble Cu2O quantum dots.
[0080] (2) Preparation of CuCoO2 powder: ① Dissolve 15 mmol Cu(NO3)2·3H2O and 15 mmol Co(NO3)2·6H2O in a mixture of 28 mL deionized water and 42 mL ethanol, and stir to form a homogeneous solution.
[0081] ② Add 4.4 g (110 mmol) of sodium hydroxide to the homogeneous solution and stir until the sodium hydroxide is completely dissolved to form the reaction precursor.
[0082] ③ The reaction precursor was placed in a polytetrafluoroethylene high-temperature reactor and sealed. The reactor was then placed in an oven set at 160℃ and kept at that temperature for 30 hours. After the reaction was complete, the reaction product was allowed to cool, and the supernatant was poured off. The precipitate was washed six times alternately with deionized water and anhydrous ethanol. After washing, the precipitate was placed in an oven at 50℃ and dried for 12 hours to obtain pure CuCoO2 powder.
[0083] (3) Preparation of CuCoO2 / Cu2O quantum dot composite materials: ① Weigh 0.013g of Cu2O quantum dots and place them in a centrifuge tube. Add 3mL of methanol and use ultrasound to treat the solution until no aggregated Cu2O quantum dots are observed in the solution, thus obtaining a uniformly dispersed Cu2O quantum dot dispersion solution.
[0084] ② Pour the Cu2O quantum dot dispersion solution into a mortar, add 0.247g of CuCoO2 powder, and grind the solution to ensure uniform mixing of the Cu2O quantum dots and the CuCoO2 powder substrate. During the grinding process, the solvent gradually evaporates to allow the solid particles to come into physical contact.
[0085] ③ After grinding until the solvent has completely evaporated, a dry powder is obtained. The dry powder is transferred to a crucible and placed in a tube furnace. Under a nitrogen atmosphere, it is heated to 350℃ at a heating rate of 5℃ / min and held at this temperature for 1.5h to promote good bonding between the quantum dots and the substrate material. After the sample cools naturally, the CuCoO2 / Cu2O quantum dot nanocomposite material is obtained.
[0086] pass Figure 5 It can be seen that the photocatalytic degradation ability of pure phase CuCoO2 for TCH is relatively weak. After introducing Cu2O quantum dots, the photocatalytic degradation efficiency of the CuCoO2 / Cu2O composite sample is significantly improved.
[0087] Example 5 This embodiment uses the same method as Example 1 to prepare CuCoO2 / Cu2O quantum dot nanocomposite material, the difference being that Cu2O is added to petroleum ether to obtain a uniformly dispersed Cu2O quantum dot dispersion solution.
[0088] In this embodiment, since petroleum ether is more volatile, the grinding time is shorter than that in Example 1, and the photocatalytic performance of the prepared composite material is similar to that in Example 1.
[0089] Example 6 This embodiment uses the same method as Example 1 to prepare CuCoO2 / Cu2O quantum dot nanocomposite material, the difference being that Cu2O is added to cyclohexane to obtain a uniformly dispersed Cu2O quantum dot dispersion solution.
[0090] In this embodiment, since cyclohexane is more volatile, the grinding time is longer than in Example 1, but the photocatalytic performance of the prepared composite material is similar to that of Example 1.
[0091] Example 7 This embodiment uses the same method as Example 1 to prepare CuCoO2 / Cu2O quantum dot nanocomposite material, the difference being that Cu2O is added to toluene to obtain a uniformly dispersed Cu2O quantum dot dispersion solution.
[0092] In this embodiment, since toluene is more volatile, the grinding time is longer than in Example 1, but the photocatalytic performance of the prepared composite material is similar to that of Example 1.
[0093] Example 8 This embodiment uses the same method as Example 1 to prepare CuCoO2 / Cu2O quantum dot nanocomposite material, the difference being that Cu2O is added to chloroform to obtain a uniformly dispersed Cu2O quantum dot dispersion solution.
[0094] In this embodiment, chloroform has a relatively higher density than n-hexane, requiring a longer time to disperse Cu2O quantum dots, but the photocatalytic performance of the prepared composite material is close to that of Example 1.
[0095] Example 9 This embodiment uses the same method as Example 2 to prepare CuCoO2 / Cu2O quantum dot nanocomposite material, the difference being that Cu2O is added to isopropanol to obtain a uniformly dispersed Cu2O quantum dot dispersion solution.
[0096] In this embodiment, since isopropanol is more volatile than water, the grinding time is shorter than that in Example 2, and the photocatalytic performance of the prepared composite material is basically the same as that in Example 2.
[0097] Comparative Example This comparative example uses the same method as Example 1 to prepare CuCoO2 / Cu2O quantum dot nanocomposites, except that low-temperature annealing is not performed in this comparative example.
[0098] XRD experiments were performed on the Cu2O quantum dots, CuCoO2 powder, and CuCoO2 / Cu2O quantum dot nanocomposites prepared in Examples 1 and 2 of this invention, and the results are as follows: Figure 1 , 2 As shown.
[0099] pass Figure 1It can be seen that the diffraction peaks of oil-soluble Cu2O quantum dots match well with the standard card (PDF#97-018-0846), and the characteristic peaks belong to the (111) and (200) crystal planes; the diffraction peaks of pure phase CuCoO2 correspond to the standard card (PDF#74-1855) of hexagonal CuCoO2, and the characteristic peaks correspond to the (006), (012), (104), and (018) crystal planes, respectively. Both single samples are pure phases. The CuCoO2 / Cu2O quantum dot nanocomposite material shows the characteristic diffraction peaks of CuCoO2 and Cu2O at the same time, and there are no additional impurity peak signals, which confirms that the present invention has successfully constructed a heterojunction structure in which the two phases coexist, and the composite process has not changed the crystal structure of the two phases and no impurity phase has been generated.
[0100] pass Figure 2 It can be seen that the diffraction peaks of water-soluble Cu2O match well with the standard card (PDF#97-018-0846), and the characteristic peaks belong to the (111) and (200) crystal planes; the diffraction peaks of pure phase CuCoO2 correspond to the standard card (PDF#74-1855) of hexagonal CuCoO2, and the characteristic peaks correspond to the (006), (012), (104), and (018) crystal planes, respectively. Both single samples show good crystallinity and phase purity. The CuCoO2 / Cu2O quantum dot nanocomposite material shows the characteristic diffraction peaks of CuCoO2 and Cu2O at the same time, and there are no additional impurity peak signals, which confirms that the present invention has successfully constructed a heterojunction structure with two phases coexisting, and the composite process has not changed the crystal structure of the two phases and no impurity phase has been generated.
[0101] The photocatalytic degradation performance of tetracycline hydrochloride (TCH) was tested on the pure phase CuCoO2 and CuCoO2 / Cu2O composite materials prepared in Examples 1, 2, 4, and the comparative examples of this invention. A 300W xenon lamp from Zhongjiao Jinyuan Company was used as the light source, which can provide full-spectrum illumination.
[0102] First, 0.02 g of pure CuCoO2 and CuCoO2 / Cu2O composite sample powder were weighed and added to 100 mL of a 40 mg / L TCH solution, respectively. Degradation experiments were then conducted at a constant temperature of 10°C. Before the light was turned on, the sample was magnetically stirred in the dark for 60 minutes to promote adsorption-desorption equilibrium between the TCH molecules on the sample surface and in the solution. After the light was turned on, 4 mL of solution was taken every 15 minutes, centrifuged for 10 minutes to remove the solid catalyst, and the absorbance of the supernatant was measured using a UV spectrophotometer. The TCH concentration was accurately determined based on the characteristic absorption peak intensity of tetracycline hydrochloride.
[0103] pass Figure 3As can be seen, in Example 1, the photocatalytic degradation ability of single pure phase CuCoO2 for TCH is weak. After introducing Cu2O quantum dots, the photocatalytic degradation performance of the prepared CuCoO2 / Cu2O quantum dot nanocomposite material is significantly improved.
[0104] pass Figure 4 As can be seen, in Example 2, the single pure phase CuCoO2 showed the weakest photocatalytic degradation ability for TCH, achieving only about 24% pollutant removal efficiency after 150 min of irradiation. The catalytic activity of the comparative sample was improved to a certain extent, with a TCH degradation rate of 62% after 150 min. This is because after the grinding solvent evaporated, the two phases initially came into contact and formed a heterojunction prototype, promoting the separation and migration of photogenerated charge carriers. The sample in Example 2 showed the best photocatalytic degradation performance, with a total TCH degradation efficiency of 95% after 75 min of irradiation. This is because annealing promoted the formation of a tightly bonded heterojunction interface between the two phases, significantly reducing the interface charge migration impedance and effectively achieving efficient separation and migration of photogenerated electron-hole pairs.
[0105] pass Figure 5 It can be seen that in Example 4, the photocatalytic degradation ability of single pure phase CuCoO2 for TCH is relatively weak. After introducing Cu2O quantum dots, the photocatalytic degradation efficiency of the CuCoO2 / Cu2O composite sample is significantly improved.
[0106] In summary, the preparation method of this invention can effectively avoid the problems of thermal decomposition, surface charge interference, and impurity phase formation that are easily generated in the preparation of quantum dot composite materials on CuCoO2 substrate. For the first time, a CuCoO2 / Cu2O quantum dot composite material with high purity, complete structure, and good interface was successfully prepared. The CuCoO2 / Cu2O quantum dot composite material exhibits excellent photocatalytic performance.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing CuCoO2 / Cu2O quantum dot composite material, characterized in that: The preparation method includes the following steps: (1) Disperse Cu2O quantum dots in a solvent and perform ultrasonic treatment to obtain a Cu2O quantum dot dispersion solution, wherein oil-soluble Cu2O quantum dots are dispersed in an oily solvent and water-soluble Cu2O quantum dots are dispersed in water or alcohol; (2) Add CuCoO2 powder to the Cu2O quantum dot dispersion solution in step (1), and then grind the solution until all the solvent evaporates to obtain dry powder; (3) In an inert gas atmosphere, the dried powder in step (2) is subjected to low-temperature annealing to obtain CuCoO2 / Cu2O quantum dot composite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the oily solvent includes one of petroleum ether, n-hexane, cyclohexane, toluene, and chloroform.
3. The preparation method according to claim 1, characterized in that: In step (1), the alcohol includes one of ethanol, methanol, and isopropanol.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of CuCoO2 powder to Cu2O quantum dots is CuCoO2:Cu2O = 4:1~19:
1.
5. The preparation method according to claim 1, characterized in that: In step (3), the annealing temperature is 300-400℃ and the holding time is 1.5-2.5h.
6. The preparation method according to claim 1, characterized in that: The specific preparation process of oil-soluble Cu2O quantum dots in step (1) Includes the following steps: S1: Dissolve Cu(NO3)2·3H2O in ethylene glycol, add polyvinylpyrrolidone and oleic acid, sonicate and stir to make the solution homogeneous; The solid-liquid ratio of Cu(NO3)2·3H2O to ethylene glycol is Cu(NO3)2·3H2O: ethylene glycol = 1 mmol: 20~30 mL. Polyvinylpyrrolidone (PVP) is added for every 1 mmol of Cu(NO3)2·3H2O, and 0.5 mL of oleic acid is added for every 1 mmol of Cu(NO3)2·3H2O. S2: Add sodium borohydride solution dropwise to the solution in step S1, stir until the reaction is complete, wash and dry the reaction product to obtain oil-soluble Cu2O quantum dots; The stirring speed is 700~900 r / min, and the reaction time is 20~30 min; The concentration of the sodium borohydride solution is ≥0.02 g / mL. The sodium borohydride solution is added to the solution in step S1 at a rate of 0.15 g of sodium borohydride per 1 mmol Cu(NO3)2·3H2O.
7. The preparation method according to claim 1, characterized in that: The specific preparation process of water-soluble Cu2O quantum dots in step (1) Includes the following steps: Q1: Dissolve Cu(NO3)2·3H2O in ethylene glycol, add polyvinylpyrrolidone and oleic acid, sonicate and stir to make the solution homogeneous; The solid-liquid ratio of Cu(NO3)2·3H2O to ethylene glycol is Cu(NO3)2·3H2O: ethylene glycol = 1 mmol: 20~30 mL. Polyvinylpyrrolidone (PVP) is added for every 1 mmol of Cu(NO3)2·3H2O, and 0.5 mL of oleic acid is added for every 1 mmol of Cu(NO3)2·3H2O. Q2: Add sodium borohydride solution dropwise to the solution in step Q2, stir until the reaction is complete, wash and dry the reaction product I, and then disperse the reaction product I in n-hexane to obtain the reaction product I solution. The stirring speed is 700~900 r / min, and the reaction time is 20~30 min; The concentration of the sodium borohydride solution is ≥0.02 g / mL. Sodium borohydride solution is added to the solution in step Q1 at a rate of 0.15 g sodium borohydride per 1 mmol Cu(NO3)2·3H2O. Q3: Dissolve 3-mercaptopropionic acid in methanol to obtain a 3-mercaptopropionic acid solution. Add the reaction product I solution from step Q2 dropwise to the 3-mercaptopropionic acid solution, and add acetone at the same time. After the reaction is completed, wash and dry the reaction product II to obtain water-soluble Cu2O quantum dots. The solid-liquid ratio of 3-mercaptopropionic acid to methanol is 3-mercaptopropionic acid:methanol = 0.1 mmol:5 mL, the molar ratio of the amount of reaction product I added to 3-mercaptopropionic acid is reaction product I:3-mercaptopropionic acid = 1:0.2, and the volume of acetone added is 3-4 times the volume of methanol.
8. The preparation method according to claim 1, characterized in that: The specific preparation process of CuCoO2 powder in step (2) Includes the following steps: A: Dissolve Cu(NO3)2·3H2O and Co(NO3)2·6H2O in a mixture of water and ethanol, and stir to obtain a homogeneous solution; The molar ratio of Cu(NO3)2·3H2O to Co(NO3)2·6H2O is 1:
1. In the mixture, the volume ratio of water to ethanol is water:ethanol = 2:
3. The total amount of Cu(NO3)2·3H2O and Co(NO3)2·6H2O added to the mixture of water and ethanol has a solid-liquid ratio of 3mmol:7mL. B: Add sodium hydroxide to the homogeneous solution in step A and stir to obtain the reaction precursor; The molar ratio of sodium hydroxide added to Cu(NO3)2·3H2O is NaOH:Cu(NO3)2·3H2O = 22:3; C: The reaction precursor in step B is subjected to a hydrothermal reaction to obtain a precipitate. The precipitate is washed and dried to obtain CuCoO2 powder. The hydrothermal reaction temperature is 120~160℃, and the reaction time is 24~36h.
9. The CuCoO2 / Cu2O quantum dot composite material prepared by the preparation method according to any one of claims 1-8, characterized in that: In the CuCoO2 / Cu2O quantum dot composite material, Cu2O quantum dots are loaded onto CuCoO2.